Ujaran Kebencian Dalam Al-Qur'an - Syakur, Mahlail (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2021)
This study is the result of qualitative research on verses of the Qur'an through library research. This study aims to determine the concept of utterance of hatred in the Qur'an, its narrative form, and the response of the Qur'an to the behavior of hate speech. The object is the verses of the Qur'an which contain narratives of hate speech and the verses that respond to them. The main source is al-Qur`an. The method of analysis uses the interpretation of tahliliy to conclude that 28 verses of the Koran show hate speech in the form of euphemism, 23 verses show the form of hate speech dysphemism, 8 verses show the form of hate speech labeling, and 7 verses show hate speech in the form of stereotypes.